Management of Intra-operative Chyle Leak during Neck Dissection: Recognition and Control - Brett Tracy; Guy J Petruzzelli (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Chyle fistula (CF) is a rare complication of neck dissection. The extravasation of chyle can result in potentially devastating metabolic, nutritional and immunologic sequellae.  We report the efficacy a protocol for treatment of intraoperative (CF).  Hospital length of stay, time to oral alimentation, and type of diet were analyzed.  There were 19 patients with thoracic duct injury development following neck dissection (0.08%) The mean age was 62 years and the majority were male with squamous cell carcinoma of the oral cavity. The TDI's were identified on the left side in 16 patients and on the right side in 3 patients. In all cases TDI were identified intraoperatively, packed with micro-fibrillar collagen and oversewn with monofilamemnt nylon. In one patient required re-exploration and placement of a muscle flap. The mean number of days NPO was 2.5 (range 1 to 13 days, SD ± 2.8). The mean LOS was 4 days (range 2 to 14 days, SD ± 2.7). Only patient number 5 and 12 required MCT administration for 14 and 12 days and no patients required parenteral nutrition.  Prompt recognition and defi nitive intraoperative management of TDI can result in reduced postoperative complications and early return to acceptable oral alimentation.